LIFELONG LEARNING AND ACTIVE CITIZENSHIP: THE CASE OF DIRECTING LIFE CHANGE PROJECT - Chandler, Keith; Siguencia, Luis Ochoa; Ochoa-Daderska, Renata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Learning is our vehicle for change. As a learning community project, we can engage mature people to learn, initially through reflection, that they are empowered to, and can still influence, the direction of their life path. Choices including creative entrepreneurship, active citizenship through volunteering and mentoring, taking up further learning and address the emerging key societal challenge of the need for citizens to be and remain proactive. The aim of this paper is to emphasis in this process and to show how, ‘Directing Life Change’11 project empowers through direct participation, not only of other Learners, with whom relationships are fostered, but also with active participation of potential Life Change actors, locally and internationally. It also seeks to share innovation and experiences with a range of different audiences.